Negotiating crisis in the new media environment: Evolution of crises online, gaining legitimacy offline - PANG, Augustine (Institutional Knowledge at Singapore Management University, 2012)
This study examines how crises originate online, how different new media platforms escalate crises, and how issues become legitimized offline when they transit onto mainstream media. We study five social media crises, which includes United breaks guitars and Southwest Air’s too fat to fly. Crises are triggered online when stakeholders are empowered by new media platforms that allow user-generated content to be posted online without any filtering. Facebook, YouTube and Twitter emerge as top crises breeding grounds due to their large user base and the lack of gatekeeping. Facebook and blogs are responsible for escalating crises beyond the immediate stakeholder groups. Mainstream media, legitimizes issues offline when there are inherent news values like, human-interest, policy-making, celebrity or novelty factors present. This study suggests recommendations to manage reputational impact on organizations and instruct practitioners on how they can use different new media tools to counter crises online and manage the transition of crises to mainstream media.